Developing a Tool to Analyze Communication Access in Restaurants for Individuals Who Use Augmentative and Alternative Communication - (:unkn) unknown (My University, 2023)
Communication accessibility has been defined by many scholars and organizations, but it is generally described as clear communication that everyone can access and understand. The objective of this research thesis is to create a tool for assessing communication accessibility for people who use augmentative and alternative communication (PWUAAC) within a variety of restaurant settings. Through a two-part study, researchers interviewed 5 adults who use AAC (Study A) and created a survey rated by an additional 10 adults who use AAC (i.e., Study B). The interviews from Study A were qualitatively coded and revealed common communication accessibility themes that restaurants and restaurant staff were not implementing, such as direct communication, respect, and ample wait and response time. This information from the interviews, alongside current AAC research literature and communication accessibility guidelines from organizations in other countries, was used to create a checklist to evaluate the communication accessibility of restaurants. In Study B, a survey was created for participants to evaluate the content of the checklist. Results from Study B indicated communication accessibility topics of high and low priority, which were utilized to scale down the length of the checklist. The implications of the final checklist from the survey include its potential usage in training restaurant staff and management to utilize communication accessibility tips and features to increase the communication accessibility of the restaurant patrons they serve, especially for individuals who use AAC.
Keywords: AAC; augmentative and alternative communication; communication accessibility; people who use augmentative and alternative communication; restaurant accessibility